Revisiting procedural human rights : fundamentals of civil procedure and the changing face of civil justice / editors: A. Uzelac, C.H. van Rhee. - Uzelac, Alan; Rhee, C. H. van (Ius commune europaeum ;, 2017)
The idea of human rights as fundamental rights of every person is certainly one of the most powerful ideas of our modern age. Since the American and French revolutions, human rights have been the strongest link between law and democracy. They have played a crucial role when defining notions of constitutionalism and the rule of law. While some human rights have been made famous in national mottos such as the French liberté, égalité et fraternité, other human rights have not attracted such attention. Generally, substantive human rights have been discussed and appreciated more than procedural human rights. Yet, without an effective and well-balanced set of procedural rights, the substantive rights and freedoms of almost any person or business would not enjoy effective protection before the courts of law. Based on the wish to reopen an international comparative discussion on fundamental notions of civil procedure, this book offers a number of insights into procedural human rights from different jurisdictions and different points of view. While some previous studies focused on Northern Europe, many of the authors in this book come from Southern and Eastern Europe, areas where a common understanding of procedural human rights may be an even more pressing necessity.